Investigating the factors affecting the profitability of Saudi Industrial Companies by using DuPont Model - Altahtamouni, Farouq; Almutawa, Ryoof; Alyousef, Shikhah (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to investigate the factors affecting the profitability of Saudi industrial companies for the period from 2011 to 2015. The DuPont model was used to measure the factors that affect both return on assets (ROA) and return on equity (ROE), using both simple and multiple linear regression tests. The results of the study showed a statistically significant effect of profit margin on (ROA), and no effect of assets turnover rate on (ROA). The results of the study showed a decrease in the explanatory power of the variables of the (ROA) model as there are other variables that explain the change in the (ROA). The results also showed a statistically significant effect of (ROA) and financial leverage on (ROE), and these variables explain 87.6% of the changes in the ROE model.
Keywords: Profitability; Return on assets; Return on equity; Dupont Model